T1 Mapping in Discrimination of Hypertrophic Phenotypes: Hypertensive Heart Disease and Hypertrophic Cardiomyopathy. (December 2015) - Hinojar, Rocio; Varma, Niharika; Child, Nick; Goodman, Benjamin; Jabbour, Andrew; Yu, Chung-Yao; Gebker, Rolf; Doltra, Adelina; Kelle, Sebastian; Khan, Sitara; Rogers, Toby; Arroyo Ucar, Eduardo; et al.
Abstract : Background—: The differential diagnosis of left ventricular (LV) hypertrophy remains challenging in clinical practice, in particular, between hypertrophic cardiomyopathy (HCM) and increased LV wall thickness because of systemic hypertension. Diffuse myocardial disease is a characteristic feature in HCM, and an early manifestation of sarcomere–gene mutations in subexpressed family members (G+P− subjects). This study aimed to investigate whether detecting diffuse myocardial disease by T1 mapping can discriminate between HCM versus hypertensive heart disease as well as to detect genetically driven interstitial changes in the G+P− subjects. Methods and Results—: Patients with diagnoses of HCM or hypertension (HCM, n=95; hypertension, n=69) and G+P− subjects (n=23) underwent a clinical cardiovascular magnetic resonance protocol (3 tesla) for cardiac volumes, function, and scar imaging. T1 mapping was performed before and >20 minutes after administration of 0.2 mmol/kg of gadobutrol. Native T1 and extracellular volume fraction were significantly higher in HCM compared with patients with hypertension ( P <0.0001), including in subgroup comparisons of HCM subjects without evidence of late gadolinium enhancement, as well as of hypertensive patients LV wall thickness of >15 mm ( P <0.0001). Compared with controls, native T1 was significantly higher in G+P− subjects ( P <0.0001) and 65% of G+P− subjects had a native T1 value >2 SD above the mean of the normal range. Native T1 was an independent discriminator between HCM and hypertension, over and above extracellular volume fraction, LV wall thickness and indexed LV mass. Native T1 was also useful in separating G+P− subjects from controls. Conclusions—: Native T1 may be applied to discriminate between HCM and hypertensive heart disease and detect early changes in G+P− subjects. Abstract : Supplemental Digital Content is available in the text.